The effects of oil prices on confidence and stock return in China, India and Russia - Melike E. Bildirici (Quantitative Finance and Economics, 2018)
This study aims to investigate the relationships between oil price, business confidence and stock return for China, India and Russia by employing the Markov Switching Vector Auto Regressive(MS-VAR) and MS-Granger Causality(MS-GC) methods. For China, the causality relationship between business confidence and stock return differ from the results of Russia and India. For China, while there is unidirectional causality from stock return to business confidence for all regimes, in India there is the evidence of bidirectional causality in all regimes. For Russia, there is the evidence of a bidirectional causality between business confidence and stock return in the first regime, while there is none causality in the second regime. In all regimes for the selected countries, there is the evidence of a unidirectional causality from oil price to stock return. But there are different results between oil price and business confidence. The different results obtained for the selected countries are explained by the three different factors. One of the reasons is that the differences in oil reserves of the countries. The other one is the differences in oil demand of the countries' economies. The last one is that the selected countries have different business confidence that can be affected by various parameters of the economy.